1991
DOI: 10.1083/jcb.114.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate, a novel lipid, involved in cellular proliferation.

Abstract: Abstract. Sphingosine, a metabolite of membrane sphingolipids, regulates proliferation of quiescent Swiss 3T3 fibroblasts (Zhang, H ., N. E. Buckley, K. Gibson, and S. Spiegel . 1990. J. Biol. Chem. 265:76-81) . The present study provides new insights into the formation and function of a unique phospholipid, a metabolite of sphingosine, which was unequivocally identified as sphingosine-l-phosphate . The rapid increase in 32P-labeled sphingosine-l-phosphate levels induced by sphingosine was concentration depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
403
2
4

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(422 citation statements)
references
References 39 publications
13
403
2
4
Order By: Relevance
“…Similarly, different outcomes may be found when the same sphingolipid is added into the culture medium of different cell lines. For instance, sphingosine 1-phosphate stimulates cell proliferation of fibroblasts, whereas it induces growth arrest in breast cancer cells [39,40]. In addition, this sphingolipid can trigger apoptosis in HL60 and Hep3B cells [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, different outcomes may be found when the same sphingolipid is added into the culture medium of different cell lines. For instance, sphingosine 1-phosphate stimulates cell proliferation of fibroblasts, whereas it induces growth arrest in breast cancer cells [39,40]. In addition, this sphingolipid can trigger apoptosis in HL60 and Hep3B cells [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…For phosphorylation of sphingosine by cultured mouse embryonic fibroblasts, the cells, prepared as described previously (37), were washed with phosphate-free Dulbecco's modified Eagle's medium and subsequently incubated with this medium containing 32 P i (40 Ci/ml) for 24 h as described previously (36). The cells were then incubated with 10 M sphingosine or vehicle (controls) for 1 h, and S1P was extracted from the cells (38,39).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue homogenates (5-20 g of protein in sphingosine kinase buffer: 50 mM Tris (pH 7.5), 10% glycerol, 1 mM ␤-mercaptoethanol, 1 mM EDTA, 1 mM sodium orthovanadate, 40 mM ␤-glycerophosphate, 15 mM NaF, 10 g/ml leupeptin and aprotinin, 1 mM phenylmethylsulfonyl fluoride, and 0.5 mM 4-deoxypyridoxine) were incubated with 50 M sphingosine (prepared either in mixed micelles with Triton X-100 or in bovine serum albumin complexes without Triton X-100), 10 Ci of [␥-32 P]ATP (1 mM), and 10 mMMgCl 2 . Labeled lipids were extracted and resolved by TLC as described previously (35,36). Labeled S1P was quantified with a PhosphorImager.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular content of sphingosine 1-phosphate (S 1 P), a phosphorylated product of sphingosine by sphingosine kinase, was accumulated in response to plateletderived growth factor in Swiss 3T3 fibroblasts [4]. Furthermore, it was demonstrated that S 1 P is involved in the regulation of cellular processes including cell proliferation [5][6][7][8][9]. Recently, several lines of evidence have accumulated suggesting that sphingolipid metabolites may function as a new class of intracellular second messenger.…”
Section: Sphingosinementioning
confidence: 99%